Comparative cross-sectional study on the prevalence, determinants and willingness to use long-acting reversible contraception among female students attending public and private universities in Ekiti State, Southwest Nigeria - Tope Michael Ipinnimo; Taofeek Adedayo Sanni; Kabir Adekunle Durowade; Olusegun Elijah Elegbede; Kayode Rasaq Adewoye; Oluseyi Adedeji Aderinwale; John Olujide Ojo; Ayo Kamal Alabi; Richard Dele Agbana; Joy Bosan (BMJ Open)
Objectives Long-acting reversible contraception (LARC) provides continuous pregnancy prevention to women for a period of 3 to 12 years, and it is very safe and effective. The aim of this study was to determine the prevalence, determinants and willingness to use LARC among undergraduate female students attending public and private universities in Ekiti State, Southwest NigeriaDesign This survey employed a cross-sectional comparative study design.Setting Public and private universities in Ekiti State, Southwest Nigeria.Participants 418 female students in their undergraduate years at public and private universities (208 students in public universities and 210 students in private universities).Primary and secondary outcomes A semistructured questionnaire was used to gather data, and analysis was done using IBM SPSS V.25. Prevalence, willingness and determinants of LARC were determined and compared between public and private universities at the level of bivariate analysis using χ2. Multivariate regression analysis was used to determine the predictor of LARC use. The statistical significance level was placed at a p value of <0.05.Results The mean age of female undergraduate students was higher in public universities (21.1±2.5 years) than in private universities (19.3±2.1 years). The prevalence of LARC usage among the sexually active respondents was 12.5% for public universities and 12.7% for private universities. Determinants and predictors of LARC uptake among the students in both university settings were age, marital status and good knowledge of LARC. Only about one quarter (24.0% in public universities and 24.8% in private universities) were willing to take up LARC among the students in both settings.Conclusion The prevalence and willingness to take up LARC in the public and private universities are still low. Determinants and predictors of LARC uptake include age, marital status and good knowledge of LARC.